L'immagine visibile di un Dio che può essere: Michel Henry e Richard Kearney in dialogo - Ford, Jonah (Aisthema, 2015)
This article attempts an exploration of Michel Henry's I Am the Truth and Richard Kearney's The God Who May Be, as each appropriate the Husserlian critique of Kantian epistemology. Although Henry and Kearney both develop a Christian theology rooted in this Husserlian inheritance, their explication of the truths Christianity asserts is strikingly different. It is the assertion of this essay that this difference is primarily a textual one; or, to put it another way, it is conditioned first by their scriptural gaze.